2013
DOI: 10.1038/ni.2682
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced interstitial migration of effector CD4+ T cells is dependent on integrin αV

Abstract: Leukocytes must traverse inflamed tissues to effectively control local infection. Although motility in dense tissues appears to be integrin-independent actin-myosin based, during inflammation changes to the extracellular matrix (ECM) may necessitate distinct motility requirements. Indeed, we found that T cell interstitial motility was critically dependent on RGD-binding integrins in the inflamed dermis. Inflammation-induced deposition of fibronectin was functionally linked to increased αv integrin expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
175
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(183 citation statements)
references
References 55 publications
7
175
1
Order By: Relevance
“…In lymph nodes, integrins are not required for interstitial migration of leukocytes, 1 whereas integrins appear to be important for their migration in inflamed tissues as shown by Overstreet et al 4 Tissues with active immune responses due to infection by pathogens, injury, or chronic tissue inflammation are different from normal tissues in tissue structure. Active immune responses increase cytokines that activate tissue cells to produce or modify ECM components such as collagen and fibronectin.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In lymph nodes, integrins are not required for interstitial migration of leukocytes, 1 whereas integrins appear to be important for their migration in inflamed tissues as shown by Overstreet et al 4 Tissues with active immune responses due to infection by pathogens, injury, or chronic tissue inflammation are different from normal tissues in tissue structure. Active immune responses increase cytokines that activate tissue cells to produce or modify ECM components such as collagen and fibronectin.…”
mentioning
confidence: 99%
“…Because of the roles of integrins in cell adhesion to extracellular matrix proteins such as collagens, fibronectin and vitronectin, searches for integrins that can guide cell migration in specialized tissues and conditions continued. Recently, Overstreet et al 4 reported that aV-containing integrins play important roles in interstitial T-cell migration in inflamed tissues. 4 The integrin chain (Itg) aV can pair with Itg b1, b3, b5, b6 and b8 to make functional heterodimers on cell membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although naïve T cells are activated in cell-dense lymphoid organs where collagen fibers are encased in fibroblastic reticular cells, they function within protein-rich peripheral tissues (Nourshargh et al, 2010). Integrins, and downstream cytoskeletal machinery, are required for lymphocyte extravasation and interstitial migration through inflamed peripheral tissue (Overstreet et al, 2013), and T cells are found in close association with matrix fibers in skin, brain and tumors (Boissonnas et al, 2007;Mrass et al, 2006;Wilson et al, 2009). The distinct extracellular biophysical properties at sites of T cell activation and function indicate that T cells themselves acquire distinct, intrinsic biophysical properties to enable migration and function within these microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor β (TGF-β) has been shown to induce αEβ7 expression on T RM cell precursors, and expression of αEβ7 integrin is required for T RM subsets to be retained within mucosal tissues and epidermal epithelia (6). In an experimental model of cutaneous leishmaniasis, blocking integrin αv in vivo increased the burden of Leishmania major parasites in the skin; moreover intravital multiphoton imaging indicated that the failure to control parasite infection was associated with inhibition of the αv integrin-dependent interstitial motility of T cells in the inflamed dermis (7).…”
mentioning
confidence: 99%